Virus-Associated Arthritis: Globalisation of Vectors and Viruses - Enßer, Armin (Aktuelle Rheumatologie, 2018)
Although the majority of cases can still be attributed to travellers returning from epidemic and endemic areas, changes in the distribution of insect vectors will increase the frequency of locally acquired infections and minor outbreaks of "tropical" viruses in Southern and Central Europe. Virus-associated arthritis is a characteristic feature of an acute infection with the Chikungunya virus. A number of other tropical and endemic pathogens as well as early forms of rheumatoid arthritis and other autoimmune diseases should be included in the differential-diagnostic evaluation.
EVALuna2:35281